(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In the article, the results of a study of touching possibilities of blind primary school children to identify sport objects (balls, maces, sport sticks) by the shape, sizes, texture of surface and other features are presented. It is stated that primary school children who are totally blind and blind with residual vision have low indicators of touching identification of main characteristics and surface texture of different sport objects, despite the fact that blind children with residual vision stay significantly behind of the totally blind peers by the studied indicators. It is specifically obvious in case of 1-2-year school children. The data from scientific literature, practice and our studies indicate that a special attention should be devoted to the study and development of touching abilities and skills of blind school children in the issues of active participation of these students in playing, study, sport-gym and other types of activities. The results of the conducted studies allow to state the necessity of elaboration of special means, methods and conditions to use them in sport-gym lessons to develop the abilities of children with visual impairment to identify the shape, size, surface texture of objects. This will promote the active participation of blind students in sport-gym lessons.